The role of website stimuli of experience on engagement and brand advocacy - Bilro, R.G.; Loureiro, S. M. C.; Faizan Ali (Journal of Hospitality and Tourism Technology, 2018)
Purpose – This study aims to examine the relationships between stimuli of website experience (information/content, interactive features and design–visual appeal) and online engagement (cognitive processing, affection and activation) with consumer-generated media and brand advocacy. Furthermore, this study examines if online engagement mediates the relationships between website stimuli of experience dimensions and brand advocacy. Design/methodology/approach – A total of 183 valid online questionnaires were collected, from members of an online forum related to travel and leisure, to empirically test the measurement and structural model using partial least square path modeling. The study sample includes consumers who search for, select and book hotel rooms via Booking.com. Findings – The findings confirm that information/content and design–visual appeal have a significant impact on all three dimensions of online engagement whereas interactive features of a website have significant impact on affection and activation. Furthermore, results suggest that affection and activation predict brand advocacy and engagement mediates the effect of stimuli of experience on brand advocacy. Originality/value – This is the first attempt to explain the relationships between website stimuli of experience (information/content, interactive features and design–visual appeal), online engagement (cognitive processing, affection and activation) and brand advocacy. Altogether, these variables are not well studied and understood in current literature despite having important implications for managers, academicians and consumers alike.